Low-cost biosorbent hybrid hydrogels for paraquat remediation of water - Baigorria, Estefanía [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier, 2022)
The excessive and indiscriminate use of agrochemicals, such as paraquat (PQ), leads to numerous water pollution problems. The adsorption of aqueous contaminants is one of the most effective methodologies for water purification. This study develops nanocomposite biopolymeric hydrogels of chitosan and clay, and examines the biosorption capacity of PQ from aqueous matrices. The main objective of the work is to achieve a biocomposite with great biosorbent characteristics and low cost. The nanocomposite hydrogels were synthesized by simple techniques and characterized by aqueous absorption capacity, differential scanning calorimetry, thermogravimetric analysis, infrared spectroscopy, X-ray diffraction, microscopic and texture techniques, and surface charge analysis. Besides, their performance in the removal of PQ from aqueous systems was studied in discontinuous tests under different conditions. The results showed maximum adsorption capacities of 0.06, 0.98, 0.94 and 0.99 mg·g−1 for CS, CS/DDA, CS/Bent and CS/LVF beads, respectively. The results showed that the presence of clay is essential for PQ sorption to occur. Thermodynamic, kinetic, and isothermal studies of the nanocomposite beads indicated that biosorption occurred spontaneously and that it has the participation of exothermic physisorption and chemisorption processes, corresponding mainly to the pseudo-second-order kinetic model, and to the Langmuir and Freundlich isothermal models. The CS hydrogel showed a non-spontaneous sorption process associated with the physisorption of PQ on the beads. The tests showed hopeful results for the utilization of the developed nanocomposite hydrogels as PQ biosorbents, with novel properties and low-cost characteristics, which are a sustainable and promising solution for the generation of pollutant-free water.
Keywords: Adsorption; Chitosan; Nanoclays; Nanocomposites; Pesticides; Water remediation